Anonymous sister [videorecording (DVD)] (Gravitas Ventures, 2023)
When a young woman turns to the camera for refuge, she ends up with a firsthand account of the deadliest manufactured epidemic in U.S. history. This is Jamie Boyle's chronicle of her family's collision with the opioid epidemic.